2018
DOI: 10.1177/1359105318787010
|View full text |Cite
|
Sign up to set email alerts
|

Emotion regulation contributes to the well-being of patients with autoimmune diseases through illness-related emotions: A prospective study

Abstract: This prospective study aimed to examine whether illness-related negative emotions mediate the relationship of cognitive reappraisal and expressive suppression to the well-being of 99 patients with rheumatoid arthritis or multiple sclerosis. After adjusting for disease and patient-related parameters, only cognitive reappraisal was associated with physical and psychological well-being through emotions. Expressive suppression was associated with psychological well-being only for patients reporting less use of cog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Other studies included emotion regulation as a part of emotion-focused coping strategies (e.g., COPE Inventory; Carver, Scheier, & Weintraub, 1989) and thus, were not reviewed due to the different conceptualization and measurement. This points to the unclarity and confusion in regarding the associations between emotion regulation patterns and psychological distress were reported in studies among patients with other severe health conditions (Karademas et al, 2011(Karademas et al, , 2018; this inconsistency also could be seen in the present study. Another point that needs attention is that most of the studies reviewed were crosssectional (Classen et al, 1996;Cohen, 2013;Ho et al, 2004;Kulpa et al, 2016;Owen et al, 2006;Peh et al, 2016Peh et al, , 2017Schroevers et al, 2011;Tamagawa et al, 2013).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Other studies included emotion regulation as a part of emotion-focused coping strategies (e.g., COPE Inventory; Carver, Scheier, & Weintraub, 1989) and thus, were not reviewed due to the different conceptualization and measurement. This points to the unclarity and confusion in regarding the associations between emotion regulation patterns and psychological distress were reported in studies among patients with other severe health conditions (Karademas et al, 2011(Karademas et al, , 2018; this inconsistency also could be seen in the present study. Another point that needs attention is that most of the studies reviewed were crosssectional (Classen et al, 1996;Cohen, 2013;Ho et al, 2004;Kulpa et al, 2016;Owen et al, 2006;Peh et al, 2016Peh et al, , 2017Schroevers et al, 2011;Tamagawa et al, 2013).…”
Section: Discussionsupporting
confidence: 52%
“…Also, cognitive reappraisal was found to be associated with low psychological distress among individuals with cardiovascular disease (Karademas, Tsalikou, & Tallarou, 2011) or diabetes (Mocan, Iancu, & Băban, 2018). In contrast, other studies found no significant associations between suppression or cognitive reappraisal and psychological distress among individuals with chronic conditions such as rheumatoid arthritis, multiple sclerosis (Karademas et al, 2018) or psoriasis (Ciuluvica, Fulcheri, & Amerio, 2019). Suppression and experiential avoidance were associated with higher psychological distress in individuals with other conditions, such as cardiovascular diseases (Goodwin & Emery, 2016;Karademas et al, 2011) or fibromyalgia (Bowers, Wroe, & Pincus, 2017).…”
Section: -3mentioning
confidence: 93%
“…Similarly, the relationship between childhood adversity and perceived stress in adulthood was weakest at high levels of PCR (Kalia & Knauft, 2020), indicating a buffering role on the relationship between stressor exposure and negative outcomes. Generally, in stressor-exposed samples, the same positive relationships with positive affect (Gillanders et al, 2008; Haverstock et al, 2020; Katana et al, 2019; Litzelman et al, 2017), well-being (Hopp et al, 2011; Katana et al, 2019), perceived quality of life (Li et al, 2015), sense of control (Haverstock et al, 2020), and questionnaire-assessed trait resilience (Baghjari et al, 2017), as well as negative relationships with negative affect (Gillanders et al, 2008; Haverstock et al, 2020; Karademas et al, 2018; Katana et al, 2019) and perceived stress (Haverstock et al, 2020; Katana et al, 2019) can be found.…”
Section: Resultsmentioning
confidence: 78%
“…Research on patients’ use of intrapersonal emotion regulation is mostly focused on how their use of these strategies is associated with their symptoms and recovery (i.e. Aldao et al, 2014; Karademas et al, 2020), and how emotion regulatory training effects their emotion recognition and expression abilities (Cho and Jang, 2019). This research does not consider emotion regulation in the context of therapeutic relationships.…”
Section: Introductionmentioning
confidence: 99%